Visualizing Generalized Computational Experiment State - Захарова, А.А.; Коростелев, Д.А.; Podvesovskii, A.; Галактионов, В.А. (Графикон - конференции по компьютерной графике и зрению, 2021)
The paper considers the problem of evaluating the state of a generalized computational experiment in the context of a general problem of creating methods for adaptive planning and control of a generalized computational experiment in mathematical modeling of real physical processes. A generalized computational experiment implies multiple solution of the numerical simulation problem for various sets of values of defining model parameters. As a method for assessing a generalized computational experiment state, it is proposed to visualize a set of experimental data specifying this state then followed by analysis of the resulting visual image. An approach to visualization of a generalized computational experiment state is proposed based on the sequential applying of two methods: visualization of a series of dependencies of the output simulation parameters on the input ones for a given set of approximating functions and visualization of approximation accuracy parameters for different ranges of values of the input parameters. A description of each of these methods is given. Examples of their application are considered when assessing the accuracy of numerical models of the OpenFOAM software platform for a three-dimensional problem of inviscid flow around a cone.
Keywords: Generalized computational experiment; generalized computational experiment state; multidimensional data; visualization; visual analytics; approximation; problem of flow around a cone; OpenFOAM